OPTIMIZATION OF CARBON NANOTUBES AS ADDITIVE IN LUBRICANT - LIM, SHI YI (2012)
Carbon nanotube (CNT) has a high potential in automotive lubricating application due to its ultra small size and stiffness that can contribute towards better anti-wear and anti-friction properties. Conventional additives such as molybdenum dithiocarbamates and zinc dialkyldithiophosphates can cause heavy emission of the pollutants such that their usage is limited. This in turn will result in an inefficient engine that can increase the fuel consumption and produce excessive emission. Thus there is a demand for an alternative additive in order to alleviate the environmental problem. With CNTs as the alternative additive, specific characteristics are required in order to improve the lubricant performance. The objective of the work is to study the effect of the growth parameters on CNTs properties namely diameter size and crystallinity in order to produce CNTs with optimum characteristics using floating catalytic chemical vapour deposition. The growth parameters investigated were the weight of ferrocene, flow rate of ethylene and argon, and the reaction temperature. Samples of CNTs produced were characterized using scanning electron microscopy, transmission electron microscopy, thermo-gravimetric analysis, X-Ray diffraction and Raman spectroscopy. Temperature of 850°C under 20 seem of ethylene with 0.1 g ferrocene is the optimum condition for CNT growth with the diameter range of 29-70 nm and crystallinity (Id/Ig) of 0.54. Different weight percentage (0.01wt% to 0.10wt%) of crude, purified multiwall CNTs produced using optimum conditions and commercialized single-wall CNT sample were incorporated into the lubricant, MACH 5 PETRONAS in order to conduct the four-balls-wear test and ball-on-disc test. Significant reduction (71%) in the diameter of wear scar can be achieved with the incorporation of 0.02 wt% of crude MWCNTs into the lubricant. With this crude MWCNTs sample, a loading of 392 N can reduce the friction coefficient by 54%. Under the loading of 20N a reduction offriction coefficient from 0.099 to 0.0222 can be achieved. This study gave a great approach to rationalize CNTs as alternative additive in lubricant by providing promising results in friction and wear reduction.